2018
DOI: 10.1093/jrr/rrx093
|View full text |Cite
|
Sign up to set email alerts
|

Typical doses and dose rates in studies pertinent to radiation risk inference at low doses and low dose rates

Abstract: In order to quantify radiation risks at exposure scenarios relevant for radiation protection, often extrapolation of data obtained at high doses and high dose rates down to low doses and low dose rates is needed. Task Group TG91 on ‘Radiation Risk Inference at Low-dose and Low-dose Rate Exposure for Radiological Protection Purposes’ of the International Commission on Radiological Protection is currently reviewing the relevant cellular, animal and human studies that could be used for that purpose. This paper pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(34 citation statements)
references
References 44 publications
0
33
0
1
Order By: Relevance
“…Exemplary HDR values were 0.3 Gy/min (Grosovsky and Little 1985), 0.3 Gy/min (Ueno et al 1982), 0.4 Gy/min (Manesh et al 2014), 0.5 Gy/min (Furuno-Fukushi et al 1988), 0.5 Gy/min (Lorenz et al 1994), 0.5 Gy/min (Nakamura and Okada 1981), 0.70-0.79 Gy/min (Russell et al 1958), and 0.83 Gy/min (Evans et al 1990). These values are much lower than the tens of Gy/min following the atomic bomb detonations in Hiroshima and Nagasaki (Ruhm et al 2018). The results presented in this report suggest that the biological effectiveness of gamma radiation increases when the dose rate reaches ca 8 Gy/min.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Exemplary HDR values were 0.3 Gy/min (Grosovsky and Little 1985), 0.3 Gy/min (Ueno et al 1982), 0.4 Gy/min (Manesh et al 2014), 0.5 Gy/min (Furuno-Fukushi et al 1988), 0.5 Gy/min (Lorenz et al 1994), 0.5 Gy/min (Nakamura and Okada 1981), 0.70-0.79 Gy/min (Russell et al 1958), and 0.83 Gy/min (Evans et al 1990). These values are much lower than the tens of Gy/min following the atomic bomb detonations in Hiroshima and Nagasaki (Ruhm et al 2018). The results presented in this report suggest that the biological effectiveness of gamma radiation increases when the dose rate reaches ca 8 Gy/min.…”
Section: Discussionmentioning
confidence: 99%
“…With respect to stochastic effects, the sparing effect of reducing the dose rate below the HDR range is far less clear. This problem is now in the focus of interest, because of discussions regarding the validity of the DDREF (Ruhm et al 2016 , 2018 ). Because epidemiological studies on cohorts exposed to low dose rate radiation are not able to provide a clear answer (Hoel 2018 ), studies have been carried out with animals and in vitro cell systems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One might argue that the exposure of the atomic bomb survivors is not really relevant here, because cumulated exposure from CT scans is due to low-energy X-rays and might be distributed over several single exposures, while the atomic bomb survivors were exposed to high-energy gamma radiation (plus some contributions from neutrons) and within a single very short period. Indeed, the mean energy of gamma radiation that was present at the bombings of Hiroshima and Nagasaki was of the order of several MeV (Rühm et al 2018a) which is much higher than typical energies of diagnostic X-ray examinations. A recent report of the National Council on Radiation Protection and Measurements (NCRP) has reviewed the biological effectiveness of low-energy photons for evaluating human cancer risk and found that radiation used in X-ray diagnostics might be a factor of about 1.5 more effective than 1.25 MeV gamma radiation emitted by the decay of 60 Co (NCRP 2017).…”
Section: Are Studies On Atomic Bomb Survivors Relevant In the Presentmentioning
confidence: 95%
“…The accidents at nuclear power plants in Chernobyl and Fukushima resulted in chronic low-dose-rate radiation exposure for a large number of people, although the exposures in Fukushima were much lower than those in Chernobyl (1,2). These incidents motivated essential research to better understand the health effects of such exposure and to develop strategies for alleviating the possible long-term radiation effects.…”
Section: Introductionmentioning
confidence: 99%